Influence of the administration form of menthol in physical performance in endurance exercise: A systematic review - Neto, M. M.; da Silva, R. S.; Silva, A. S. (Science & Sports, 2023)
Objectives Perform a systematic review of the literature and present the results of randomized clinical trials (RCTs) pointing out under which conditions and forms of administration menthol is really capable of improving performance in endurance exercise.